Using QuizWhizzer to Improve Descriptive Reading Comprehension - Kamilah, Nuha; Panuntun, Ida Ayu (Universitas Muhammadiyah Magelang, 2026)
This study aims to improve descriptive reading comprehension and student engagement among eleventh-grade students in Class XI-H3 at SMAN 4 Pekalongan through the use of the game-based learning platform, QuizWhizzer. The research employs a Classroom Action Research (CAR) framework based on the Kemmis and McTaggart model, consisting of planning, acting, observing, and reflecting. Data were gathered through testing (pre-test and post-tests) and non-testing methods (field notes and observation sheets) and analyzed using a mixed-methods approach (descriptive quantitative and qualitative). The results indicate that the integration of QuizWhizzer, combined with collaborative discussions, successfully increased the student mastery rate from 61.29% in the pre-test to 91.43% in Cycle I, peaking at 94.12% in Cycle II. Furthermore, student engagement improved significantly from 58.33% in Cycle I to 89.58% in Cycle II. It is concluded that the integration of QuizWhizzer with collaborative instructional strategies is an effective instrument for enhancing descriptive reading comprehension and student learning motivation.